Periprosthetic UHMWPE Wear Debris Induces Inflammation, Vascularization, and Innervation After Total Disc Replacement in the Lumbar Spine - Veruva, Sai Y.; Lanman, Todd H.; Isaza, Jorge E.; Freeman, Theresa A.; Kurtz, Steven M.; Steinbeck, Marla J. (Clinical orthopaedics and related research, 2017)
Background The pathophysiology and mechanisms driving the generation of unintended pain after total disc replacement (TDR) remain unexplored. Ultrahigh-molecular-weight polyethylene (UHMWPE) wear debris from TDRs is known to induce inflammation, which may result in pain. Questions/purposes The purpose of this study was to determine whether (1) periprosthetic UHMWPE wear debris induces immune responses that lead to the production of tumor necrosis factor-α (TNFα) and interleukin (IL)-1ß, the vascularization factors, vascular endothelial growth factor (VEGF) and platelet-derived growth factor-bb (PDGFbb), and the innervation/pain factors, nerve growth factor (NGF) and substance P; (2) the number of macrophages is associated with the production of the aforementioned factors; (3) the wear debris-induced inflammatory pathogenesis involves an increase in vascularization and associated innervation. Methods Periprosthetic tissues from our collection of 11 patients with contemporary TDRs were evaluated using polarized light microscopy to quantify UHMWPE wear particles. The major reason for revision (mean implantation time of 3 years [range, 1–6 years]) was pain. For control subjects, biopsy samples from four patients with degenerative disc disease with severe pain and autopsy samples from three normal patients with no history of back pain were also investigated. Immunohistochemistry and histology were used to identify secretory factors, macrophages, and blood vessels. Immunostained serial sections were imaged at ×200 magnification and using MATLAB and NIH ImageJ, a threshold was determined for each factor and used to quantify positive staining normalized to tissue sectional area. The Mann-Whitney U test was used to compare results from different patient groups, whereas the Spearman Rho test was used to determine correlations. Significance was based on p < 0.05. Results The mean percent area of all six inflammatory, vascularization, and innervation factors was higher in TDR tissues when compared with normal disc tissues. Based on nonparametric data analysis, those factors showing the most significant increase included TNFα (5.17 ± 1.76 versus 0.05 ± 0.03, p = 0.02), VEGF (3.02 ± 1.01 versus 0.02 ± 0.002, p = 0.02), and substance P (4.15 ± 1.01 versus 0.08 ± 0.04, p = 0.02). The mean percent area for IL-1ß (2.41 ± 0.66 versus 0.13 ± 0.13, p = 0.01), VEGF (3.02 ± 1.01 versus 0.34 ± 0.29, p = 0.04), and substance P (4.15 ± 1.01 versus 1.05 ± 0.46, p = 0.01) was also higher in TDR tissues when compared with disc tissues from patients with painful degenerative disc disease. Five of the factors, TNFα, IL-1ß, VEGF, NGF, and substance P, strongly correlated with the number of wear particles, macrophages, and blood vessels. The most notable correlations included TNFα with wear particles (p < 0.001, ρ = 0.63), VEGF with macrophages (p = 0.001, ρ = 0.71), and NGF with blood vessels (p < 0.001, ρ = 0.70). Of particular significance, the expression of PDGFbb, NGF, and substance P was predominantly localized to blood vessels/nerve fibers. Conclusions These findings indicate wear debris-induced inflammatory reactions can be linked to enhanced vascularization and associated innervation/pain factor production at periprosthetic sites around TDRs. Elucidating the pathogenesis of inflammatory particle disease will provide information needed to identify potential therapeutic targets and treatment strategies to mitigate pain and potentially avoid revision surgery. Level of Evidence Level III, therapeutic study.